2020
DOI: 10.5812/archcid.95563
|View full text |Cite
|
Sign up to set email alerts
|

Toxoplasmosis and Risk of Endothelial Dysfunction: Role of Oxidative Stress and Pro-Inflammatory Mediators

Abstract: Background: Infection with Toxoplasma gondii (T. gondii) leads to activation of T-helper cells (Th-1 and Th-2) which are involved in the synthesis and release of different cytokines which may lead to endothelial dysfunction. Objectives: To evaluate the endothelial function in patients with acute toxoplasmosis. Methods: This case-control study involved 31 patients with toxoplasmosis aged 19 -47 years matched with 20 healthy subjects. Anti-T. gondii antibody (IgG, IgM, IgA) was determined by direct antigen-antib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 28 publications
0
14
0
Order By: Relevance
“…The pathophysiology of toxoplasmosis is known to be related to the increased risk of oxidative stress in host cells due to the activation of inflammatory response against the parasite [59]. One of the critical host defence methods against intracellular parasites is oxidative stress generated by the immune system [60,61].…”
Section: Discussionmentioning
confidence: 99%
“…The pathophysiology of toxoplasmosis is known to be related to the increased risk of oxidative stress in host cells due to the activation of inflammatory response against the parasite [59]. One of the critical host defence methods against intracellular parasites is oxidative stress generated by the immune system [60,61].…”
Section: Discussionmentioning
confidence: 99%
“…Some authors reported a significant increase in the concentration of MDA in the serum of humans with chronic toxoplasmosis. Kiran et al [ 47 ], Al-Kuraishy et al [ 85 ] and Yazar et al [ 53 ] reported that MDA levels were significantly higher in asymptomatic Toxoplasma seropositive patients compared to healthy subjects. There was no correlation between age or gender and the MDA concentration.…”
Section: Oxidative Stress In Toxoplasma Gondii Infectionmentioning
confidence: 99%
“…The pathophysiology of toxoplasmosis is known to be related to the increased risk of oxidative stress in host cells due to the activation of inflammatory response against the parasite [ 85 ]. In chronic acquired toxoplasmosis, the level of MDA is elevated and can reflect indirectly the degree of oxidative cell damage [ 54 ].…”
Section: Plant-derived Antioxidants In Toxoplasmosis Treatmentmentioning
confidence: 99%
“…Antioxidants including superoxide dismutase activity, glutathione peroxidase activity, catalase activity, vitamin C, vitamin E, glutathione and albumin concentrations significantly grow high in the serum of the toxoplasmosis aborted women, which is characterized by the free radical released with infection causing increased the oxidative stress (16) . Toxoplasmosis was reported to be associated with the stimulation and progress of pregnancy induced-hypertension because of oxidative stress and endothelial dysfunction (17) . Increased production of free radicals leads to more lipid peroxidation and then higher oxidative damage in cellular membranes, which includes placental membrane damage due to lipid peroxidase inhibiting the synthesis of prostaglandin I2 enzyme, thus causing this enzyme to malfunction, and then the vessels shrink causing hematopoietic and platelet aggregation (18) .…”
Section: Introductionmentioning
confidence: 99%